Penetapan Kadar Asam Retinoat Pada Krim Anti Acne di Kabupaten Blora dengan Spektrofotometri UV - Andieni , Herdania Puan; Kusumowati, Ika Trisharyanti Dian (Journal of Pharmaceutical and Sciences, 2026)
Acne is a skin disorder characterized by chronic inflammation involving the sebaceous glands and excessive bacterial colonization. Management of acne generally requires external treatment, focusing on maintaining facial hygiene using facial cleansers supported by the use of anti-acne products. Anti-acne creams are cosmetic products formulated with active ingredients that help prevent and treat acne. One of the active ingredients commonly used in such products to improve acne-prone skin conditions is retinoic acid. Based on BPOM RI 2007, that use of retinoic acid requires a doctor’s prescription. The purpose of this study to identify the levels of retinoic acid in anti-acne cream product circulating in the Blora regency area. Qualitative testing using Thin Layer Chromatography (TLC) method obtained 1 sample out of 5 containing retinoic acid. Based on the calculating of validation parameters, the equation Y = 0.1488x – 0.0026 with a correlation coefficient (r)of 0.993, exLOD 0.554 ppm, LOQ 1.681 ppm, %RSD 1.8895% and %Recovery 83.823 – 109.503%. The calculating of the levels in sample that positive for containing retinoic acid, sample E obtained at 0.103036%, which exceeds the limit established in the National Formulary.